Changes in homocysteine levels during normal pregnancy and preeclampsia and its relation with oxidative stress - A. V., Shilpa; P. A., Zubaida; G., Rajalekshmi (International Journal of Research in Medical Sciences, 2016)
Background: Preeclampsia is a pregnancy specific disorder characterised by vasospasm and endothelial dysfunction. One of the most favoured hypotheses is the endothelial dysfunction secondary to the peroxidation of membrane lipids resulting in altered vascular reactivity, loss of vascular integrity and activation of the coagulation cascade. Elevated circulating homocysteine is a risk factor for endothelial dysfunction and vascular diseases and is found to be associated with preeclampsia. Hyperhomocysteinemia increases the risk of atherosclerosis through a mechanism involving oxidative damage. Malondialdehyde, (MDA) a metabolite of lipid peroxides detectable in plasma is used as an indicator of lipid peroxidation. Methods: The present study was undertaken to find out the alterations in the circulating levels of serum homocysteine and malondialdehyde (MDA) in normal pregnancy and preeclampsia when compared to normal nonpregnant women. The case control study was conducted by taking a statistical sample size of 30 subjects (18- 35 years) in each group. Data were analyzed using ANOVA. Significance level was fixed at p<0.05. Results: The mean serum levels of homocysteine were higher in preeclampsia patients than normal pregnant women. The mean serum levels of MDA in preeclampsia patients were higher than that of normal pregnant women. Conclusions: The increased homocysteine levels in preeclampsia results in endothelial dysfunction and vasospasm. Also oxidative stress plays an important role in the pathogenesis of preeclampsia. Thus identifying the risk factors and aggressive management may prove to be beneficial in these women.